Insertion and role of women in the cassava agrosystem (Research, Society and Development, 2022)
In the Brazilian rural area, the high social inequality makes the gender division at work stronger, because even when participating in agricultural activities, women are always seen as "helpers", being stereotyped in domestic service. Therefore, the objective of this study was to diagnose the insertion and performance of women in the cassava agrosystem in the Soledade community, municipality of Moju-PA. Data collection was carried out through the application of quantitative and qualitative questionnaires, using “snowball” sampling. The collected data were treated using descriptive statistics and processed with Microsoft Excel 2010 software. According to the results, it was found that: of 100% of respondents, only 33.33% are feminine. Regarding jobs between men and women, 87% of producers believe in the distinction of jobs for both. Regarding the activities carried out in the productive units, 66.67% are carried out by men. As for the activities performed by women, it was identified that 66.67% perform the activities of Plantation, weeding, scraping and coercion. Regarding the activities developed by men in the productive stages, it was found that 66.67% developed them (Drilling, felling, slashing, planting, weeding, harvesting, scraping, roasting).conclusion of this study is that: Women share production spaces with men in the cassava production chain, with a distinction being made between what is an activity for men and women; Jobs considered “heavy” are assigned to men, and “light” jobs are assigned to women; There is a lack of recognition of participation, and appreciation of the work performed by women in cassava.